Quality of Life Depending on Gender - Djabbarova Nafisa Mamasoliyevna; Kobilova Nigina Akmalovna; Khusainova Munira Alisherovna (Peerian Journals Publishing, 2022)
Assessment of quality-of-life indicators, such as physical, psychological, emotional and social well-being in patients with combined cardiovascular pathology is of great scientific and practical importance. The possibility of correcting these disorders in the process of complex pharmacotherapy of patients with combined cardiovascular pathology is an urgent task of modern cardiology. The quality of life, according to WHO definition, is a characteristic of physical, psychological, emotional and social functioning based on its subjective perception. QOL indicators, as well as the characteristics of the disease picture, vary over time depending on the patient's condition, which allows monitoring of the treatment being carried out, and, if necessary, to carry out its correction. The patient's participation in the assessment of his condition is also a valuable and reliable indicator of the current state. To obtain comparable data and their further its applications in clinical practice use standard QOL assessment tools, which are questionnaires (indexes and profiles). In the USA and Special centers have been established in Europe to develop such questionnaires.
Keywords: Myocardial infarction; gender characteristics; coronary heart disease in women; quality of life